High BRAF V600 Mutation Level Associated with Worse Outcome in Metastatic Melanoma Patients Receiving BRAF and MEK Inhibitors - Ariane Fizazi; Chris Serrand; Alexandre Evrard; Blanche Bergeret; Pierre-Emmanuel Stoebner; Myriam Marque (Acta Dermato-Venereologica)
The prognostic value of BRAF V600 mutation level on clinical outcomes in patients with BRAF V600-mutated metastatic melanoma treated with BRAF and MEK inhibitors remains uncertain. The association was retrospectively analysed between BRAF V600 mutation level (defined as the ratio of the quantification of the BRAF V600 allele to the percentage of tumoral cells in the sample analysed) and progression-free and overall survival (PFS and OS, respectively) and 3-month response rate in a cohort of 58 patients with metastatic melanoma who harboured BRAF V600E/K mutations and received dual targeted-therapy BRAF/MEK inhibitors. The BRAF mutation level cut-off determined by the area under the receiver operating characteristic curve after internal validation by bootstrap methods was 0.44. Risk of poor PFS and OS was associated with BRAF V600 mutation level > 0.44 on multivariate analysis (p = 0.02 and p = 0.02, respectively) after adjusting for major confounding factors (age, sex, lactate dehydrogenase level, brain metastasis, and treatment line). No association was found between BRAF mutation level and 3-month response rate. Our study shows that high BRAF V600 mutation level in melanoma tissue was associated with poor prognosis in patients with metastatic melanoma treated with BRAF and MEK inhibitors.